Design Optimization of SiC-CMOS Inverter for Space Applications - Kavita Lalwani (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The ever-increasing requirements of integrated circuits in space application demands critical research for new devices/circuits, which have potential to withstand Single Event Effect (SEE) under radiation environments. Lightweight satellites require high-density integrated circuits. Currently, silicon based CMOS ICs are used for this purpose. Goal of the proposed work is the design optimization of SiC-CMOS IC and to study its performance in high temperature conditions and in the space radiation environment. In this work, feasibility studies on the performance validation such as IV characteristics, switching characteristics, gain and voltage transfer curve of SiC-MOSFET and SiC-CMOS inverters are carried out in TCAD simulations (COGENDA) for space applications. The optimized design parameters and performance parameters will help us to develop the SiC-CMOS based physical ICs for future ISRO space crafts.